Sistem Informasi Inventori Puskesmas Berbasis Web (Studi Kasus : Puskesmas Simpang Baru): Web-Based Health Center Inventory Information System (Case Study: Simpang Baru Community Health Center) - Habil, M Habil Arsyiddik Tanjung (Indonesian Journal of Informatic Research and Software Engineering (IJIRSE), 2021)
The current application of technology in the field of inventory can simplify all tasks, especially processing inventory datawhich requires speed, accuracy and data validity. Inventory Information System is a system that provides inventory reportinformation in the form of a transaction history of incoming or outgoing goods, thus helping to process large inventorydata quickly, precisely and efficiently. The problems that occur in processing patient inventory data at the Simpang BaruCommunity Health Center are currently still manual, namely using Microsoft Excel, where the incoming and outgoinggoods data are stored in Excel, after inputting a lot of data, then the next step is to print the inventory report. The items tobe printed must first be created with existing tables, so users have to search for data by scrolling up and down so that it is difficult to find a lot of data and check one by one existing data so it takes a lot of time. The information system at theSimpang Baru Community Health Center in Pekanbaru City was designed with an analysis technique and a descriptiveObject Oriented Analysis Design (OOAD) method. This information system is designed using PHP and MySQL which isused as a solution to solving problems in processing inventory data at the health center. It is hoped that this informationsystem will be more organized and can simplify working methods, increase work efficiency, assist in storing data, andspeed up the transaction process of health center goods.